Mental Health At The Workplace: An Online Exploratory Study On Perceived Stress, Common Mental Disorder, And Sleep During COVID-19 Pandemic - Sharma, P; Pokharel, M; Sharma, P; Sharma, S; Acharya, S (Journal of Psychiatrists’ Association of Nepal, 2020)
Introduction: Stress in the workplace is a well-known phenomenon. With the current COVID-19 pandemic and the measures to counteract it has led to a psychological toll on employees of almost all sectors. We aim at exploring the self-perceived stress, screen for anxiety, and depression, and sleep problems among the employees of a corporate business house. Material And Method: An online survey using a cross-sectional design and purposive sampling was conducted during the lock-down due to the COVID-19 pandemic in Nepal among the employees of a corporate house before conducting a stress management session. The tools used were semi-structured proforma and the Perceived Stress Scale (PSS), Patient Health Questionnaire-4 (PHQ4), and Single-item sleep quality scale (SQS). A descriptive statistical analysis was performed. Results: The majority of the respondents were male (64.9%), unmarried (78.9%), and lived with their family (92.8%). A moderate level of stress was present among 86.0% and a high level of stress among 5.2% of respondents. 24.6% and 33.3% of individuals were screened positive for anxiety and depression respectively. 17.5% of the individuals had poor sleep and 15.8% perceived their work efficiency was decreased. Conclusion: The stress and psychological problems reported by the respondents strongly suggest a need for regular stress management programs. Further studies are warranted with a larger sample size and from different sectors to look at the real impact of COVID-19 on the employees.